Beyond Sugar and Ethanol Production: Value Generation Opportunities Through Sugarcane Residues - Formann, Steffi; Hahn, Alena; Janke, Leandro; Stinner, Walter; Sträuber, Heike; Logroño, Washington; Nikolausz, Marcell (Frontiers in Energy Research, 2020)
Sugarcane is the most produced agricultural commodity in tropical and subtropical regions, where it is primarily used for the production of sugar and ethanol. The latter is mostly used to produce alcoholic beverages as well as low carbon biofuel. Despite well-established production chains, their respective residues and by-products present unexploited potentials for further product portfolio diversification. These fully or partially untapped product streams are (a) sugarcane trash or straw that usually remain on the fields after mechanized harvest, (b) ashes derived from bagasse combustion in cogeneration plants, (c) filter cake from clarification of the sugarcane juice, (d) vinasse which is the liquid residue after distillation of ethanol, and (e) biogenic CO2 emitted during bagasse combustion and ethanol fermentation. The development of innovative cascading processes using these residual biomass fractions could significantly reduce final disposal costs, improve the energy output, reduce greenhouse gas emissions, and extend the product portfolio of sugarcane mills. This study reviews not only the state-of-the-art sugarcane biorefinery concepts, but also proposes innovative ways for further valorizing residual biomass. This study is therefore structured in four main areas, namely: (i) Cascading use of organic residues for carboxylates, bioplastic, and bio-fertilizer production, (ii) recovery of unexploited organic residues via anaerobic digestion (AD) to produce biogas, (iii) valorization of biogenic CO2 sources, and (iv) recovery of silicon from bagasse ashes.